Perlindungan atas Merk Terkenal - Winata, Frans H. (Indonesian Journal of International Law, 2008)
The function of a mark is not only distinguish a product from another product, but also to be priceless asset for a company, especially for a well-known mark. What is still being debated today is the definition of a well-known mark. The measure to be used is still unclear. The government really needs to be pushed to immediately issue a Government Regulation regarding well-known mark. This Government Regulation on well-known marks will not only become a proof of the government’s seriousness in protecting the owner of intellectual property rights, but it will also be regarded as the government’s effort to create a conducive condition for business actors to run their business in Indonesia.